Long‐Term Gastrointestinal Consequences are Frequent Following Sporadic Acute Infectious Diarrhea in a tropical country: A Prospective cohort Study. (September 2018) - Rahman, Masudur M.; Ghoshal, Uday Chand; Sultana, Shamima; Kibria, Md Golam; Sultana, Nigar; Khan, Zeenat Arefin; Ahmed, Faruque; Hasan, Mahmud; Ahmed, Tahmeed; Sarker, Shafiqul Alam
Abstract : BACKGROUND: Postinfection irritable bowel syndrome (PI‐IBS) and functional dyspepsia (PI‐FD), though reported from the temperate countries, have not been studied in the tropics; PI‐malabsorption syndrome (MAS), which mimics PI‐IBS, is reported from the tropics. No report till date on PI‐IBS excluded PIMAS. We studied: (i) the frequency of continuing bowel dysfunction after acute gastroenteritis (AG), (ii) its predictors, and (iii) PI‐MAS among patients with PI‐IBS. METHODS: 345 consecutive subjects each, with AG and age‐ and gender‐matched healthy controls were followed up 3‐monthly for 12 months using a translated‐validated questionnaire and functional gastrointestinal disorders (FGIDs) were diagnosed by Rome III criteria. Symptom duration >3 months but <6 months was diagnosed as chronic bowel dysfunction (CBD) and dyspeptic symptoms, respectively. MAS was diagnosed if 2/3 tests ( D‐xylose H2 breath test, Sudan III‐stained stool microscopy, and duodenal histology) were abnormal. Fecal microbiological studies were performed in 245/345 (71%) patients. RESULTS: AG patients more often developed PI‐IBS and PI‐FD than controls (16.5 vs. 2.6% and 7.4 vs. 0.6%, respectively; p <0.001). Presence of FD was a risk factor for PI‐IBS and IBS for PI‐FD. On multivariate analysis, dyspeptic symptoms, CBD, and weight loss were the risk factors for PI‐FGIDs. The frequency of PI‐IBS following Vibrio cholera and other bacterial infection was comparable. Malabsorption was present among 2/23 (9%) patients with PI‐IBS. CONCLUSION: FGIDs are common after AG; dyspeptic symptoms, CBD, and weight loss were risk factors for PIFGIDs. Vibrio cholerae infection caused PI‐FGID, which was never reported. About 9 % patients fulfilling the criteria for PI‐IBS had PI‐MAS.